Diskontna mera pri uporabi metod, ki temeljijo na diskontiranem denarnem toku, za potrebe analize nepremičninskih naložb in vrednotenja nepremičnin - Pšunder, Igor (Geodetski vestnik, 2011)
During the last few decades there has been an increase in the use of methods of real estate investment and other investment analyses based on discounted cash flow. Despite the relatively wide use of discounted cash flow methods, project managers believe their own knowledge of these methods is insufficient even to the extent where this could lead to incorrect decisions (e.g. conflicting indications of the net present value method and the internal rate of return method). One of major drawbacks in the use of investment analysis methods that are based on discounted cash flow is unsatisfactory precision in the determination of the discount or the capitalization rate. Methods based ondiscounted cash flow are not only intended for project feasibility analysis;discounted cash flow serves as a basis for assessing special real estate within the mass real estate appraisal system in Slovenia. The article studies the importance of the discount rate when analysing and assessing real estate projects. The theoretical part presents the basis of discounted cash flow methods and composition of the discount rate or capitalisation rate and presents a simulation of the impact of the discount rate and capitalisation rate on investment evaluation and assessment results. The empirical part is based on a survey conducted among certified real estate appraisers in Slovenia. The survey was conducted in the second half of February and beginning of March 2011. The response rate was 32.9 percent, indicating that almost one-third of all certified appraisers in Slovenia participated. Survey data were statistically analysed and the results provide us with the discount rate and calculated risk premium and capital recovery premium for various typeof real estate. A statistical analysis of the survey data provides insights into the risk premium and capital recovery premium used for real estate appraisal and investment purpose.
Keywords: analiza nepremičninskih naložb; capital recovery premium; capitalisation rate; cash flows; denarni tokovi; discount rate; diskontna mera; investicije; investments; mera kapitalizacije; nepremičnine; net present value; neto sedanja vrednost; premija za ohranitev kapitala; premija za tveganje; real estate; real estate investment analysis; risk premium; special real estate appraisal; valuation; vrednotenje